Electrochemical Impedance Spectroscopy Microsensor Based on Molecularly Imprinted Chitosan Film Grafted on a 4-Aminophenylacetic Acid (CMA) Modified Gold Electrode, for the Sensitive Detection of Glyphosate - Zouaoui, Fares; Bourouina-Bacha, Saliha; Bourouina, Mustapha; Alcacer, Albert; Bausells, Joan; Jaffrezic-Renault, Nicole; Zine, Nadia; Errachid, Abdelhamid (Frontiers in Chemistry, 2021)
A novel electrochemical impedance spectroscopy (EIS) microsensor was implemented for the dosage of traces of glyphosate, in real and synthetic water samples. Molecularly imprinted chitosan was covalently immobilized on the surface of the microelectrode previously modified with 4-aminophenylacetic acid (CMA). The characterization of the resulting microelectrodes was carried out by using cyclic voltammetry measurement (CV), scanning electron microscopy (SEM), and electrochemical impedance spectrometry (EIS). EIS responses of the CS-MIPs/CMA/Au microsensor toward GLY was well-proportional to the concentration in the range from 0.31 × 10−9 to 50 × 10−6 mg/mL indicating a good correlation. The detection limit of GLY was 1 fg/mL (S/N = 3). Moreover, this microsensor showed good reproducibility and repeatability, high selectivity, and can be used for the detection of GLY in river water.